Inclusive Leadership: Exploring Leaders’ and Faculty’s Perspectives in Higher Education Institutions in Azerbaijan - Bashirova, Aisha (My University, 2026)
This study aimed to explore how university leaders and faculty perceive and experience inclusive leadership in higher education institutions in Azerbaijan. Globalization has increased diversity in academic environments, and inclusive leadership has emerged as a leadership style that addresses the needs of diverse academic institutions and promotes collaboration among faculty members. Although several reforms have been implemented and diversity increased in Azerbaijani higher education institutions, no previous study has explored how inclusive leadership is defined and experienced. This study is significant for providing qualitative insights into how inclusive leadership can support participatory governance and create academic environments that value diverse perspectives in the Azerbaijani higher education context. Using qualitative exploratory research design, semi-structured interviews were conducted with seven leaders and five faculty participants, selected through purposeful sampling, from three public higher education institutions. The findings reveal that university leaders primarily define inclusive leadership as involving everyone in the decision-making process, whereas faculty respondents associate it with creating a safe environment and feeling heard. The study results are consistent with Brewer’s Optimal Distinctiveness Theory and highlight the importance of balancing faculty members’ needs for belongingness and uniqueness. The study revealed several challenges to the implementation of inclusive leadership, such as resistance to change, faculty workload, and limited engagement. Reducing centralization, adopting policies to increase faculty participation, and implementing leadership training programs on collaborative governance will help promote inclusive academic environments.
Keywords: Inclusive Leadership; Higher Education; Faculty Participation; University Leadership; Participatory Governance; Decision-Making; Academic Environment